2015
DOI: 10.1136/bmjopen-2014-007520
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of chronic tic disorder and obsessive-compulsive disorder diagnoses in the Swedish National Patient Register

Abstract: ObjectivesThe usefulness of cases diagnosed in administrative registers for research purposes is dependent on diagnostic validity. This study aimed to investigate the validity and inter-rater reliability of recorded diagnoses of tic disorders and obsessive-compulsive disorder (OCD) in the Swedish National Patient Register (NPR).DesignChart review of randomly selected register cases and controls.Method100 tic disorder cases and 100 OCD cases were randomly selected from the NPR based on codes from the Internatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
122
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(125 citation statements)
references
References 16 publications
3
122
0
Order By: Relevance
“…However, the results call for a cautious interpretation, given a few limitations of the study, such as the relatively small TS sample size and the rareness of the outcome, resulting in broad confidence intervals and precluding a more detailed examination of varying causes of death, and finally the diagnoses given in a clinical setting. A recent study in Sweden, however, showed that the validity and interrater reliability of tic disorders was high in a comparable registry . Finally, we only included persons with a diagnosis of tics derived in psychiatric and somatic hospitals and outpatient clinics, which generally convey a higher rate of mortality, than samples derived in settings of primary care …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results call for a cautious interpretation, given a few limitations of the study, such as the relatively small TS sample size and the rareness of the outcome, resulting in broad confidence intervals and precluding a more detailed examination of varying causes of death, and finally the diagnoses given in a clinical setting. A recent study in Sweden, however, showed that the validity and interrater reliability of tic disorders was high in a comparable registry . Finally, we only included persons with a diagnosis of tics derived in psychiatric and somatic hospitals and outpatient clinics, which generally convey a higher rate of mortality, than samples derived in settings of primary care …”
Section: Discussionmentioning
confidence: 99%
“…A recent study in Sweden, however, showed that the validity and interrater reliability of tic disorders was high in a comparable registry. 38 Finally, we only included persons with a diagnosis of tics derived in psychiatric and somatic hospitals and outpatient clinics, which generally convey a higher rate of mortality, than samples derived in settings of primary care. 9…”
Section: Discussionmentioning
confidence: 99%
“…The ICD‐10 codes had excellent validity, with a positive predictive value of 91% (rater 1) and 96% (rater 2). The inter‐rater agreement was outstanding (kappa=0.98, p<0.001) .…”
Section: Methodsmentioning
confidence: 98%
“…This register has been heavily used in research, leading to standardized and validated protocols for selecting psychiatric populations. These protocols have been adhered to in the present investigation, with established codes (eMaterial in the Supplement) used to define cases of the following: schizophrenia, 19 bipolar disorder, 19 autism spectrum disorder (ASD), 19 anorexia nervosa, 19 substance abuse, 19 attention-deficit hyperactivity disorder (ADHD), 15 obsessive-compulsive disorder (OCD), 20 major depressive disorder (MDD), 19 social phobia, agoraphobia, 21 and generalized anxiety disorder (GAD). 21 Individuals with tic disorder were also selected, although small case numbers precluded examination of mating patterns in these populations.…”
Section: Methodsmentioning
confidence: 99%